Event-Based Eccentric Motion Detection Exploiting Time Difference Encoding - D'Angelo, Giulia; Janotte, Ella; Schoepe, Thorben; O'Keeffe, James; Milde, Moritz B.; Chicca, Elisabetta; Bartolozzi, Chiara (Frontiers in Neuroscience, 2020)
Attentional selectivity tends to follow events considered as interesting stimuli. Indeed, the motion of visual stimuli present in the environment attract our attention and allow us to react and interact with our surroundings. Extracting relevant motion information from the environment presents a challenge with regards to the high information content of the visual input. In this work we propose a novel integration between an eccentric down-sampling of the visual field, taking inspiration from the varying size of receptive fields (RFs) in the mammalian retina, and the Spiking Elementary Motion Detector (sEMD) model. We characterise the system functionality with simulated data and real data collected with bio-inspired event driven cameras, successfully implementing motion detection along the four cardinal directions.